The difference in microleakage levels of nanohybrid composite resin using eighth-generation ethanol and isopropanol solvent bonding materials under moist and dry conditions (in vitro study) - Irfan Dwiandhono; Setiadi W. Logamarta; Taura Dhanurdara (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Microleakage during restoration causes secondary caries. The shrinkage of nanohybrid composite resin can occur during the polymerization process, affected by both the selection of bonding materials featuring different solvents, such as ethanol and isopropanol, as well as contrasting conditions such as moist and dry. Purpose: This study aimed to determine and analyze the differences of microleakage level of nanohybrid composite resin using the eighth-generation bonding materials made from ethanol and isopropanol solvents under moist and dry conditions. Methods: This research constituted an experimental laboratory study. The samples were divided into four groups. Group I used a bonding material produced from ethanol under dry conditions. Group II used a bonding material produced from ethanol under moist conditions. Group III used a bonding material produced from isopropanol under dry conditions. Group IV used a bonding material produced from isopropanol under moist conditions. The levels of microleakage were subsequently tested using a stereo microscope. Results: Microleakage examination was performed by means of a stereo microscope to observe the methylene blue color penetration with assessment subsequently being performed on a scale of 0 to 3. The statistical results of a Kruskal-Wallis test showed that no significant differences occurred in any of the treatment groups (sig = 0.141, p<0.05). Conclusion: There was no difference in the microleakage levels of nanohybrid composite resin using eighth-generation bonding materials produced from ethanol and isopropanol solvents under moist and dry conditions.